Tax Authority Versus Peer Communication: The Influence of Trust, Service Climate, and Voluntary Cooperation - Tjondro, Elisa; Patuli, Lijuntri; Andrianto, Richard; Julitha, Delitha (Jurnal Ilmiah Akuntansi dan Bisnis, 2020)
This research is the first study to discuss the combined influence of peer communication and tax authority communication on taxpayers’ trust in tax institutions, perceptions of service climate, and voluntary cooperation. We also compare the influences of the tax authorities and peer communication on trust, service climate, and voluntary cooperation. The survey was conducted in 2019 and represented five major cities in Indonesia (Jakarta, Surabaya, Semarang, Bandung, and Denpasar). Respondents included 120 self-employed taxpayers in two business fields, namely, trade/production and services/professions. The respondents mainly included those from the millenial and generation X age groups due to their significant contribution to the tax revenue. Participants were recruited using quota sampling, and the data analysis tools included partial least square with Wrap-PLS software. Results show that tax authority communication is more powerful in influencing trust, perception of service climate, and voluntary cooperation, than peer communication. Keywords:  Peer communication, tax authority communication, trust, service climate, voluntary cooperation